2011
DOI: 10.1002/jor.21297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertonic dextrose injections in the rabbit carpal tunnel

Abstract: Objective This study investigated the effects of different doses of hypertonic dextrose injection on the carpal tunnel subsynovial connective tissue (SSCT) and median nerve in a rabbit model. Methods Thirty-eight New Zealand white rabbits weighing 4.0–4.5 kg were used. One forepaw carpal tunnel was randomly injected with one of five different treatments: saline-single injection; saline-two injections one week apart; 10% dextrose-single injection; 20% dextrose-single injection; or 10% dextrose- two injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 24 publications
5
40
1
1
Order By: Relevance
“…Based on previous studies [10,18], a sample size of 12 was needed in the mechanical testing group, and 25 were needed for EP testing. We estimated that eight specimens would be needed for histology and noted that the preparations for routine staining, nerve histology, and EM all required different fixation and so could not all be done on the same specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies [10,18], a sample size of 12 was needed in the mechanical testing group, and 25 were needed for EP testing. We estimated that eight specimens would be needed for histology and noted that the preparations for routine staining, nerve histology, and EM all required different fixation and so could not all be done on the same specimens.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 A rabbit CTS model has been developed in which SSCT fibrosis is induced by injection of hypertonic dextrose. 12-14 …”
Section: Introductionmentioning
confidence: 99%
“…It will eventually thicken and strengthen injured tendons and ligaments. The recent animal study confirmed the presence of fibrous tissue in the carpal tunnel after injection of hyperosmolar dextrose (21). This is a retrospective pilot study conducted on a small sample of participants.…”
Section: Discussionmentioning
confidence: 56%